VD_FINDINFO HC / 2013 / 89 vom 31. Januar 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, DÉCISION D'IRRECEVABILITÉ, CONSORITÉ, PRINCIPE DE LA CONFIANCEINTERPRÉTATION DU CONTRAT, INTERPRÉTATIONSENS GÉNÉRAL | 18 al. 1 CO, 253 CO, 70 al. 1 CPC (CH)